Availability and Use of Internet-based Library Services among Lecturers in Selected Polytechnics in Ogun State Nigeria - (:unkn) unknown (My University, 2018)
The Internet has become a vital tool in teaching, research and learning process in Nigeria higher institutions and across the whole world. Research has indicated that most users tend to begin their information searches via the internet, using various search engine such as Google, Wikipedia etc. rather than using WebPAC or Card catalogue in the library. For such users, a visit to their library is unnecessary and a waste of precious time. This has led to a great challenge in the academic libraries. This study investigate the Availability and Use of Internet Base Library Services among Lecturers in Selected Polytechnic in Ogun State Nigeria. Descriptive research design was used in this study, with the use of a structured questionnaires. The population of the study comprises all lecturers from Federal Polytechnic, Ilaro, Moshood Abiola Polytechnic and Gateway Polytechnic in Ogun State. The population to be studied is 548, due to the large number of the sample size, stratified random sampling techniques will be used to select 155. The researcher employs the use of table, frequency distribution (bar and percentages) and simple percentage for data interpretation. The study revealed that Internet-based library services are
Keywords: African Research